Predicting intrapartum fetal compromise at term using the cerebroplacental ratio and placental growth factor levels (PROMISE) study: randomised controlled trial protocol. Issue 8 (13th August 2018) - Sherrell, Helen; Clifton, Vicky; Kumar, Sailesh
Abstract : Introduction: Intrapartum complications are a major contributor to adverse perinatal outcomes, including stillbirth, hypoxic–ischaemic brain injury and subsequent longer term disability. In many cases, hypoxia develops as a gradual process due to the inability of the fetus to tolerate the stress of parturition suggesting reduced fetoplacental reserve before labour commences. The fetal cerebroplacental ratio (CPR) is an independent predictor of intrapartum fetal compromise, poor acid base status at birth and of neonatal unit admission at term. Similarly, circulating maternal levels of placental growth factor (PlGF) are lower in pregnancies complicated by placental dysfunction. This paper outlines the protocol for the PROMISE Study, which aims to determine if the introduction of a prelabour screening test for intrapartum fetal compromise combining the CPR and maternal PlGF level results in a reduction of adverse perinatal outcomes. Methods and analysis: This is a single-site, non-blinded, individual patient randomised controlled trial of a screening test performed at term, combining the fetal CPR and maternal serum PlGF. Women with a singleton, non-anomalous pregnancy will be recruited after 34 weeks' gestation and randomised to either receive the screening test or not. Screened pregnancies determined to be at risk will be recommended induction of labour. Demographic, obstetric history and antenatal data will be collected at enrolment, and perinatal outcomes will be recorded after delivery. Relative risks and 95% CIs will be reported for the primary outcome. Regression techniques will be used to examine the influence of prognostic factors on the primary and secondary outcomes. Ethics and dissemination: This study has been reviewed and approved by the Mater Human Research Ethics Committee (Reference: HREC EC00332) and will follow the principles of Good Clinical Practice. The study results will be disseminated at national and international conferences and published in peer-reviewed journals. Trial registration number: ACTRN12616001009404; Pre-results.